EFFICIENCY OF BORIC ACID TO CONTROL PASTURE SPITTLEBUGS ð˜‹ð˜¦ð˜°ð˜ªð˜´ ð˜§ð˜ð˜¢ð˜·ð˜°ð˜±ð˜ªð˜¤ð˜µð˜¢ AND ð˜•ð˜°ð˜µð˜°ð˜»ð˜¶ð˜ð˜ªð˜¢ ð˜¦ð˜¯ð˜µð˜³ð˜¦ð˜³ð˜ªð˜¢ð˜¯ð˜¢ (HEMIPTERA: CERCOPIDAE) - Nakano, Octavio; Barros, Lucas Silva; Krol, Ana Caroline Amorim (REVISTA DE AGRICULTURA, 2020)
The Urochloa spp. (sin. Brachiaria spp.) is an important grass cultivated in Brazil. However, the pasture spittlebugs pest attack can limited this forage plant supply and animal production. In search of alternative pest control methods, this research evaluated the boric acid efficiency to control spittlebugs Deois flavopicta and Notozulia entreriana (Hemiptera: Cercopidae). The experiment was carried out under completely randomized design with six treatments and four replications. The treatments were boric acid at concentrations of 0.1, 0.2 and 0.4% and insecticides permethrin 50 CE (0.005%) and imidacloprid 700 WG (0.02%). The number of surviving insects after pulverization of treatments to pasture spittlebugs pest control efficiency were performed. Boric acid at the concentration 0.4% showed 100% of efficiency to control spittlebugs D. flavopicta and N. entreriana species. Thus, boric acid at 0.4% can be used to integrated pest management programs of forage grasses.